The presentation, diagnosis and management of non-traumatic wrist pain: An evaluation of current practice in secondary care in the UK NHS - Dean, BJF; Carr, A; Trickett, RW; Kluzek, S; Riley, N; Bretherton, CP; Wilson, MK; Hayton, MJ; Rupani, NR; Hsieh, CCD; Clifton, LJ; Dacombe, P; et al. (Oxford University Press, 2020)
Objectives. The study aims were to assess the burden of non-traumatic wrist pain in terms of numbers of referrals to secondary care and to characterize how patients present, are diagnosed and are managed in secondary care in the UK National Health Service. Methods. Ten consecutive patients presenting with non-traumatic wrist pain were identified retrospectively at each of 16 participating hospitals, and data were extracted for 12 months after the initial referral. Results. The 160 patients consisted of 100 females and 60 males with a median age of 49 years, accounting for ∼13% of all new hand/wrist referrals. The dominant wrist was affected in 60% of cases, and the mean symptom duration was 13.3 months. Diagnoses were grouped as follows: OA (31%), tendinopathy (13%), ganglion (14%), ulnar sided pain (17%) and other (25%). The OA group was significantly older than other groups, and other groups contained a predominance of females. The nonsurgical interventions, in decreasing frequency of usage, were as follows: CS injections (39%), physiotherapy (32%), splint (31%) and analgesics (12%). Of those who underwent surgery, all patients had previously received non-surgical treatment, but 42% had undergone only one non-surgical intervention. Conclusions. Non-traumatic wrist pain represents a significant burden to secondary care both in terms of new patient referrals and in terms of investigation, follow-up and treatment. Those presenting with OA are more likely to be older and male, whereas those presenting with other diagnoses are more likely to be younger and female.